Bioactivities of hemorphins released from bovine haemoglobin gastrointestinal digestion: Dual effects on intestinal hormones and DPP-IV regulations. (September 2017) - Domenger, Dorothée; Caron, Juliette; Belguesmia, Yanath; Lesage, Jean; Dhulster, Pascal; Ravallec, Rozenn; Cudennec, Benoit
Highlights: Hemorphins produced during simulated haemoglobin gastrointestinal digestion. Hemorphins elevate STC-1 CCK & GLP-1 release with no significant mRNA levels change. Hemorphins downregulate STC-1 PC-1 mRNA levels. Hemorphins impact both DPP-IV activity and Caco-2 mRNA levels in vitro . Abstract: Food-derived hemorphins were studied for their interactions with intestinal cells in relation to food intake regulations. LLVV-H4, LVV-H4, VV-H4, VV-H7 and H7 were identified in the 2 h-intestinal hydrolysate of haemoglobin simulated gastrointestinal digestion and synthesised. These food-derived hemorphins showed secretagogue properties of the anorexigenic hormones cholecystokinin (CCK) and glucagon-like peptide 1 (GLP-1) when in contact with murine STC-1 cells. They did not show significant modulatory effect on the corresponding prohormones mRNA levels. However, they downregulated the enzyme PC1 that processes proglucagon into GLP-1 specifically in the intestine. Moreover, VV-H4, VV-H7 & H7 were potent inhibitors of the GLP-1 inactivating dipeptidyl-peptidase IV (DPP-IV) and transiently upregulated its mRNA in human Caco-2 cells. These results suggest that food-derived hemorphins display dual luminal effects that participate at different levels in food intake and glycaemia regulation and add to the known roles of the special class of food-derived opioid peptides, the hemorphins.